An Early Design Phase Method for Characterizing and Comparing Wave Energy Converter Archetypes - Aeron Roach; Moira Meek; Raza Ali; Bryony DuPont; Bryson Roberston (International Marine Energy Journal)
Wave energy converters (WECs) hold promise for powering blue economy applications, but their success relies on their ability to survive in the highly energetic ocean climate. Existing approaches for understanding WEC functional benefits often occur during detailed design, which can lead to crucial functional decisions based on archetype selection rather than design goals. This paper presents a methodology that leverages functional decomposition for identifying high-level overlaps between WEC archetypes during early design stages. Functional decomposition is a method for analyzing complex systems and tracking energy, information, and material flows. We apply this method to seven fully submerged WEC archetypes. This process provides helpful information for understanding the necessary functions of a submerged WEC. The methodology and case study results will help communities advance their efforts to combat climate change by selecting the best device for their application and location in the blue economy. Better identifying functional overlaps between WEC archetypes will help researchers and developers generate effective designs that build resilient coastal communities.